2004
DOI: 10.1093/deafed/enh032
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phonological and Morphological Training on Speech Perception Scores and Grammatical Judgments in Deaf and Hard-of-hearing Children

Abstract: Seventeen primary school deaf and hard-of-hearing children were given two types of training for 9 weeks each. Phonological training involved practice of /s, z, t, d/ in word final position in monomorphemic words. Morphological training involved learning and practicing the rules for forming third-person singular, present tense, past tense, and plurals. The words used in the two training types were different (monomorphemic or polymorphemic) but both involved word final /s, z, t, d/. Grammatical judgments were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Targeting articulation directly may also be beneficial. Moeller et al, (2010) and Bow et al, (2004) showed that when articulation skills improved so did morphological production and/or perception. Presentation of targets in utterance final position and manipulation of the phonological properties of the target word may also enhance accuracy during the early stages of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting articulation directly may also be beneficial. Moeller et al, (2010) and Bow et al, (2004) showed that when articulation skills improved so did morphological production and/or perception. Presentation of targets in utterance final position and manipulation of the phonological properties of the target word may also enhance accuracy during the early stages of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Children who are HH have difficulties with the perception (Stelmachowicz, Pittman, Hoover & Lewis, 2001, 2002; Bow, Blamey, Paatsch, & Sarrant, 2004) and production of /s/ and /z/ as speech sounds (Elfenbein, et. al., 1994; Moeller, et al, 2010) and as grammatical morphemes (Koehlinger et al, 2013;McGuckian & Henry, 2007).…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…Children who are HH are likely to be less accurate at hearing and producing phonological forms that are implicated in English morphology (Bow et al, 2004; Moeller et al., 2010; Stelmachowicz et al, 2001, 2002). While only analyzing results from children with good word final articulation skills is a common and important control as a means of isolating morphological production difficulties, this is rarely done since it may underestimate the functional impairment faced by these children.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption that earlier access to hearing aids promotes better outcomes needs to be further examined in reference to a well-defined group of hard-of-hearing children. Studies of language intervention and language outcomes often mix results from children with cochlear implants and children with hearing aids, making it difficult to clearly identify factors affecting outcomes for the HH group (e.g., Bow, Blamey, Paatsch, Sarant, 2004; Fitzpatrick et al, 2007, Sarant et al, 2008). Stiles et al (2012) proposed that a measure of aided hearing, the Speech Intelligibility Index (SII), might provide a more realistic measure of how children access speech for use in language learning.…”
Section: Evidence Of Protective Factorsmentioning
confidence: 99%
“…Evidence from both hearing [129] and DHH populations [122] suggests that the development of phonemic awareness and reading are reciprocal or bidirectional processes that appear to support each other. In controlled studies across two different languages, children with hearing technology who received reading training showed enhanced phonological and morphological skill development [129,130]. These results suggest that the relationship between reading and phonological and morphological skill development is a complicated one that seems to work in an almost cyclical fashion that can feed off of itself One method that has been effective in assisting DHH children in accessing the phonology of their auditory language and applying it to reading is an instruction method based in visual phonics [118][119][120].…”
Section: Literacy Development In Dhh Children Who Use Hearing Aids Anmentioning
confidence: 99%